Modelos de atención a víctimas de delitos: revisión conceptual y observación de la experiencia de tres centros de victimoasistencia en la ciudad de Bogotá (2010)
This document contains a review of conceptual models of victim assistance, complemented by an empirical methodology for exploring three centers of victim-assistance because criminal and serious violations of human rights, situated in the city of Bogotá. We identified and analyzed the conceptual frameworks under which the shares have been generated in these facilities, methods of direct and indirect assistance and impact indicators. From the analysis of data obtained both by exploring empirically the conceptual elements of revised proposed and argued about a proposal to adapt models of care to victims because the criminal action from psycho-legal intervention and based in the victimology.